Solidworks Simulation of Mechanical Properties of Recycled Plastics/Nanocomposite Faces Sandwich Panels - Azeez, Ahmad T.; Mohammed, Serwan S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
Sandwich panels are lightweight, high strength materials desired by engineers for various applications. However, many contributions cited the replacement of the metallic surfaces with reinforced polymeric composites for additional weight reduction purpose but none observed for recycled plastics. Accordingly, this work plans to investigate the mechanical behavior of sandwich panels made of recycled plastic/Nano reinforced composites under tension, compression, and bending load using Solidworks simulation. The data were obtained from previous works, and the complementary data were collected using different approaches. All models revealed that polycarbonate (PC) skin dominated over polypropylene and high-density polyethylene due to the highest modulus of elasticity. However, the results indicated that the core unless reinforced the outer skins will be separated as a result of residual strain at interfaces. Consequently, the core of PC skin sandwich panel reinforced with two thin sheets which lead to improvement in loading endurance from 500 to 1500N without exceeding the allowable limits of the materials and leading to the birth of environmentally intimated material termed green sandwich panel.